The Relationship Between Menstrual Cycle and Dietary Patterns on Physical Ability Perception Among Female Taekwondo Athletes - Najwa Khairunnisa Dzakiya; Yati Ruhayati; Kuston Sultoni (Universitas Negeri Semarang, 2026)
This study examines how female taekwondo athletes perceive physical abilities, menstrual cycles, and diet. This study applied a quantitative method with a ceoss-sectional correlational design. A total of 36 female taekwondo athletes were recruited through total sampling techniques, divided into junior (n = 21) and senior (n = 15) groups. The instruments used included the International Physical Activity Questionnaire-Short From (IPAQ-SF) questionnaire to evaluate the perception of physical ability; Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to measure diet; and the Menstrual Distress Questionnaire (MEDI-Q) questionnaire to assess the menstrual cycle. Data analysis was carried out using the Pearson product moment correlation test and descriptive statistics. The results of the study revealed that in the junior group, there was no significant association between diet and menstrual cycle (r = 0.159; p > 0.05), as well as between diet and views on the perception of physical ability (r = -0.025; p > 0.05). Meanwhile, in the senior group, a meaningful relationship with moderate negative strength was identified between menstrual cycle and perception of physical ability (r = -0.516; p < 0.05). In general, these findings indicate that the association between menstrual cycles and views on physical ability is situational and is more strongly seen in senior-level athletes.